ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MERGER PADA PERUSAHAAN PUBLIK DI INDONESIA (Studi Pada Perusahaan Go Public Terdaftar di BEI) - Lelly Yanti Arumdalu; Rina Ani Sapariyah; Tri Widianto (STIE AUB Surakarta, 2018)
This study aims to provide empirical evidence that there are significant differences in the Current Ratio, Debt to Equity Ratio, Total Assets Turn Over, Retun on Assets and Net Profit Margin before and after the merger and there are significant differences in financial performance (CR, DER, TATO, ROA and NPM together) before and after the merger. The population in this study amounted to 13 companies that go public. The sample selection using census method so that the samples obtained amounted to 13 companies that go public. The data used are the company's financial statements 3 years before the merger (2010,2011,2012) and 3 years after the merger (2014,2015,2016).Methods of analysis used is the test of normality, Paired Sample T-Test and Multivariate Test. The test results using paired samples t-test asserts that the Current Ratio shows no significant differences before and after the merger, Debt to Equity Ratio shows no significant differences before and after the merger and Net Profit Margin shows no significant differences before and after the merger, while Total Assets Turn Over indicates there is a significant difference before and after the merger and Return on Assets showed there are significant differences before and after the merger. The results of multivariate testing test stated that there were significant differences on the overall financial performance before and after the merger.Keywords: Mergers, Financial Performance, Current Ratio, Debt to Equity Ratio, Total Assets Turn Over, Return on Assets, Net Profit Margin.